ANALISIS PEMBIASAAN POSITIF DI SEKOLAH DASAR SEBAGAI PENGUAT DISIPLIN SISWA DALAM KERAPIHAN SERAGAM DAN KEBERSIHAN DIRI - Safitri, Alifia; Diba Catur Putri, Fara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Positive habituation is an effective character education strategy for fostering discipline among elementary school students. This study aims to analyze the implementation of positive habituation at SDN Kebalen 01 as an effort to strengthen students’ discipline in terms of uniform neatness and personal hygiene. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, with classroom teachers serving as key informants and students as the subjects of observation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, and data validity was ensured through technique and source triangulation. The findings indicate that positive habituation was implemented in a planned and continuous manner through daily routines such as uniform neatness checks, personal hygiene inspections, classroom duties, and shared morning meals. These practices had a positive impact on improving students’ discipline, responsibility, and independence, although the internalization of discipline was not yet evenly developed among all students. Supporting factors included teachers’ consistency and a conducive school culture, while inhibiting factors involved differences in family backgrounds and limited individual guidance. This study concludes that positive habituation is an effective strategy for strengthening discipline among elementary school students when implemented consistently and supported by collaboration between schools and families.